Design and Synthesis of "All‐in‐One" Multifunctional FeS2 Nanoparticles for Magnetic Resonance and Near‐Infrared Imaging Guided Photothermal Therapy of Tumors. (6th October 2016) - Meng, Zhouqi; Wei, Fang; Ma, Wujun; Yu, Nuo; Wei, Peiling; Wang, Zhaojie; Tang, Yueqin; Chen, Zhigang; Wang, Huiping; Zhu, Meifang
Abstract : The ideal theranostic nanoplatform for tumors is a single nanoparticle that has a single semiconductor or metal component and contains all multimodel imaging and therapy abilities. The design and preparation of such a nanoparticle remains a serious challenge. Here, with FeS2 as a model of a semiconductor, the tuning of vacancy concentrations for obtaining "all‐in‐one" type FeS2 nanoparticles is reported. FeS2 nanoparticles with size of ≈30 nm have decreased photoabsorption intensity from the visible to near‐infrared (NIR) region, due to a low S vacancy concentration. By tuning their shape/size and then enhancing the S vacancy concentration, the photoabsorption intensity of FeS2 nanoparticles with size of ≈350 nm (FeS2 ‐350) goes up with the increase of the wavelength from 550 to 950 nm, conferring the high NIR photothermal effect for thermal imaging. Furthermore, this nanoparticle has excellent magnetic properties for T 2 ‐weighted magnetic resonance imaging (MRI). Subsequently, FeS2 ‐350 phosphate buffer saline (PBS) dispersion is injected into the tumor‐bearing mice. Under the irradiation of 915‐nm laser, the tumor can be ablated and the metastasis lesions in liver suffer significant inhibition. Therefore, FeS2 ‐350 has great potential to be used as novel "all‐in‐one" multifunctional theranostic nanoagents for MRI and NIR dual‐modal imaging guided NIR‐photothermal ablation therapy (PAT) of tumors. Abstract : "All‐in‐one" multifunctional FeS2 nanoparticles with size of ≈350 nm (FeS2 ‐350) are prepared and their photoabsorption intensity goes up with the increase of the wavelength from 550 to 950 nm. They can be used as a novel theranostics nanoagent for simultaneous magnetic resonance imaging (MRI) and near‐infrared dual‐modal imaging and for photothermal therapy of tumors.